Adsorbent for capturing carbon dioxide from air stream or industrial air stream, application method and mosquito trap
The novel adsorbent with grafted short-chain amines on γ-alumina and silica gel addresses moisture sensitivity and desorption issues, achieving efficient CO2 capture and mosquito trap performance across varying humidity levels.
Patent Information
- Application Number
- CN202411476349.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-10-22
AI Technical Summary
Existing carbon dioxide capture technologies using molecular sieves and amine adsorbents face challenges with moisture sensitivity, reduced adsorption efficiency at high or low humidity, and difficulty in desorption, limiting their applicability to smaller-scale scenarios and mosquito traps using ambient air as a CO2 source face issues with humidity affecting capture efficiency and adsorbent life.
A novel adsorbent prepared by grafting short-chain primary amines onto carriers like γ-alumina and silica gel through silicon-oxygen covalent bonds, ensuring high hydrophobicity and thermal stability, allowing efficient CO2 capture from air streams with humidity ranging from 30-100% and enabling rapid desorption using steam or boiling water.
The adsorbent achieves high CO2 capture efficiency with CO2-rich gas streams exceeding 80% volume, suitable for small and medium-scale operations, and maintains performance stability with minimal amine oxidation, supporting mosquito traps effective across varying humidity levels.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of gas adsorption and separation, and in particular relates to an adsorbent for capturing carbon dioxide from air flow or industrial air flow, an application method and a mosquito trap. Background Art
[0002] Pressure swing adsorption and amine absorption technologies are used to separate high-concentration CO2-containing streams, including pure CO2 streams, from industrial gas streams (CO2 content above 8% by volume), such as natural gas boiler flue gas, intermediate gas from chemical plants such as synthetic ammonia, and methanol-to-hydrogen production. This process is a mature and widely used method that has been scaled up. In recent years, carbon capture technologies have been developed to separate CO2 from air streams (CO2 content around 430 ppmv), producing streams with CO2 concentrations above 1% by volume. This technology is used in certain specific scenarios or regions, or to provide a gas source for further enrichment and utilization.
[0003] Among technologies for capturing carbon dioxide from air or industrial gas streams, adsorbing the carbon dioxide using solid adsorbents, followed by desorption via heating and pressure reduction (TVSA or VSA) is an effective and feasible method. Optional solid adsorbents include molecular sieves, loaded carbonates, and loaded amines. Molecular sieve adsorbents capture carbon dioxide primarily through physical adsorption and desorption. They are suitable for capturing carbon dioxide from industrial gas streams with high CO2 content, but not from air streams. Furthermore, because they are more susceptible to adsorbing moisture from the gas stream, they typically require pre-dehydration facilities, making them unsuitable for smaller-scale carbon dioxide capture scenarios.
[0004] The main principle of carbonate-loaded adsorbents to capture carbon dioxide is that under normal temperature conditions in the presence of water (including carbonate aqueous solutions in the pores of the adsorbent), carbonates (such as alkaline potassium carbonate and lithium carbonate) absorb carbon dioxide and react to form bicarbonate (the reaction effect is better when a small amount of solution is formed in the pores of the adsorbent). The adsorbent is then heated and depressurized, and the bicarbonate decomposes into carbonate while releasing carbon dioxide. The performance of the adsorbent is restored after cooling; US2021187480A1 provides an adsorption material of this type, which is made by loading alkali metal carbonates such as K2CO3 onto macroporous granular activated carbon by impregnation. It adsorbs carbon dioxide from an air flow at normal temperature and pressure, and then desorbs it under conditions such as 100-300 mbar (absolute pressure) and 90-135°C. This type of carbonate-loaded adsorbent can be used to capture carbon dioxide from industrial gas streams with a certain CO2 content, as well as from air streams, and is particularly suitable for smaller-scale carbon dioxide capture scenarios. However, it has the following disadvantages: a. The carbon dioxide capture effect deteriorates significantly when the air flow humidity is too high or too low (when the air flow humidity is too high, such as when the relative humidity is above 90%, the amount of liquid filled in the inner pores of the adsorbent after moisture absorption is too high; when the air flow humidity is too low, such as when the relative humidity is below 30%, the adsorbent does not absorb enough moisture or loses water rapidly; both situations result in a reduced rate of carbon dioxide adsorption); b. Carbon dioxide cannot be desorbed through steam or boiling water (resulting in water-soluble loss of carbonates and bicarbonates).
[0005] The primary principle of carbon dioxide capture by supported amine adsorbents is that the primary and secondary amino groups of the supported organic amines adsorb CO2 and react to form amine-CO2 conjugates, which adsorb CO2. A moderate amount of water vapor in the gas stream generally favors CO2 adsorption. Upon heating the adsorbent (around 100°C) and reducing the pressure, some of the amine-CO2 conjugates decompose, releasing the amine groups and emitting the CO2. Upon cooling, the adsorbent's performance recovers. Supported amine adsorbents can be used to capture CO2 from both industrial gas streams with a certain CO2 content and from air streams. Currently, supported amine-based CO2 capture agents, which are generally recognized for their overall advantages and potential based on the binding mechanism of the amine functional groups to the support, are those produced by in-situ polymerization of amine-containing monomers onto the support (Type III).
[0006] For example, US2024024849A1 discloses a renewable CO2 capture agent loaded with an amine polymer, wherein the CO2 raw gas includes flue gas or air emitted from a coal-fired power plant containing more than 10% O2; the main adsorption site in the amine polymer loaded with the CO2 capture agent is a primary amine group; the amine polymer is preferably a linear polymer based on polyallylamine (PAA) or polyvinylamine (PVAm), and its derivatives (further grafted with amine groups on some of the amine groups to generate more amine groups, preferably citrullinated and cross-linked polyallylamine); the carrier includes mesoporous silica foam (MCF), mesoporous γ-alumina, and MCF with γ-alumina coated on the inner pore surface, and preferably a carrier with an integral structure.
[0007] US20070149398A1 discloses an amine-loaded carbon dioxide adsorbent, its preparation method, and its application. The adsorbent is composed of 10-70% organic components and 30-90% inorganic components (i.e., a carrier, such as powdered silica molecular sieve SBA-15). The carrier's inner pore surface has hydroxyl groups, and the organic component, a hyperbranched polymer, is covalently bonded to the carrier surface via oxygen provided by the hydroxyl groups. The hyperbranched polymer can be a vinylamine hyperbranched polymer produced by the polymerization of cycloethylamine (also known as ethyleneimine), or a polymer having R W A polymer having an N-CR2-CR2-structure (wherein R = H or a functional group, W = 0, 1 or 2, and the functional group may contain F, Cl, Br, I, N, P, S, or O); the hyperbranched polymer may also be connected to the support surface via a -Si-O- covalent bond. Preferably, Si is further connected to a -OCH3 to form a methoxy short chain, and Si is further covalently connected to the support surface via one or two O groups.
[0008] The carbon dioxide adsorbent loaded with amine polymers disclosed in US2024024849A1 and US20070149398A1 has the advantages of large amine loading, high CO2 equilibrium adsorption capacity, and low loss of loaded amine. The CO2 equilibrium adsorption capacity in a gas stream containing 400 ppmv of CO2 and a gas stream containing 10 v% of CO2 can exceed 0.8 mol / kg of adsorbent and 1.8 mol / kg of adsorbent, respectively, and the amine nitrogen utilization rate is lower than 0.2 mol CO2 / mol N and 0.4 mol CO2 / mol N, respectively. N (which has many tertiary amine groups and is difficult to adsorb carbon dioxide due to its large steric hindrance), has a significantly reduced CO2 equilibrium adsorption capacity when the airflow humidity is too high, such as when the relative humidity is above 90%. In the actual carbon dioxide capture application cycle, since the loading amount of the amine polymer is usually more than 30wt%, it occupies a large proportion of the space in the inner pores and has a significant internal diffusion problem. Limited by the internal diffusion of the adsorbent and the generation rate of amine-CO2 complexes, the dynamic adsorption amount of CO2 is generally about 50% of the equilibrium adsorption amount, the utilization rate of amine nitrogen is correspondingly reduced, and the time of the CO2 adsorption stage is relatively long. The loaded amine polymer also has the problem of performance degradation during the repeated temperature-raising desorption process. The reasons may include: (1) some amine groups will react with certain active centers on the surface of the carrier, such as after strong adsorption, they basically lose the ability to adsorb carbon dioxide and are easily oxidized by residual O2 during temperature-raising desorption; and (2) some amine groups that have not reacted with the surface of the carrier are oxidized by O2 in the residual CO2-containing airflow and gradually lose their ability to adsorb carbon dioxide. At the same time, conventional carrier materials with conventional dimensions, easy purchase or preparation, low cost, and spherical or bar shapes are not used. Therefore, these two existing technologies are difficult to apply.
[0009] Therefore, it is necessary to develop an easier-to-use loaded amine adsorbent that can adsorb carbon dioxide with high efficiency from air streams or industrial air streams with a relative humidity of 50-100%. The loaded amine is basically not oxidized or lost during desorption by TVSA or TSA. It has advantages in CO2 capture output, operating costs and service life, and is applicable to both small-scale and large-scale carbon dioxide capture scenarios. It is best to use steam or boiling water as the desorption heat source.
[0010] In recent years, it has been discovered that air conditions containing a certain concentration of CO2 (such as above 0.2v%) have a strong inducing effect on female mosquitoes. Properly designed carbon dioxide-induced mosquito traps have good use effects. However, when using miniature carbon dioxide liquid cylinders with a volume of 2L, there are troubles in filling, replacing cylinders and purchasing carbon dioxide. It is also not suitable for semi-enclosed scenes such as indoors, which limits the application of such mosquito traps. When using carbonate-loaded adsorbents or amine-loaded adsorbents in the existing technology, using ambient air as the CO2 gas source and TVSA desorption, when the air humidity is too high, such as when the relative humidity is above 90%, the amount of carbon dioxide captured and the mosquito catching effect are significantly reduced, and the adsorbent life is affected. Summary of the Invention
[0011] To solve the above technical problems, the present invention provides an adsorbent for capturing carbon dioxide from air flow or industrial air flow, an application method and a mosquito trap.
[0012] The adsorbent for capturing carbon dioxide from air or industrial gas streams of the present invention is prepared by the following steps:
[0013] (1) The reactor and its accompanying condensation reflux system and evacuation condensation system are subjected to anhydrous treatment and nitrogen replacement; anhydrous methyl ethyl ketone is injected into the reactor as a reaction solvent, a powdered platinum / alumina catalyst is added, and stirring is continued. Anhydrous cycloethylamine is injected, and the reactor feed liquid temperature is controlled to be 35-40°C and the condensation temperature of the condensation reflux system is -15 to -20°C; phenyl monochlorosilane is continuously injected and the injection time is controlled to be 3-5 hours, and then the feed liquid continues to react for 4-5 hours; the reactor feed liquid temperature is then controlled to be 25-40°C, the condensation temperature of the condensation reflux system is 0 to 5°C, the condensation temperature of the evacuation condensation system is -15 to -20°C and the required vacuum degree, and the reactor feed liquid is distilled for 0.5-1 hour and the distillation removal amount of the feed liquid is controlled to be 10-15wt%; the distilled feed liquid in the reactor is filtered under anhydrous and air-tight conditions, and the filtrate is used as the spray impregnation liquid for the adsorbent in step (2);
[0014] The condensation reflux system and the vacuum condensation system are used in series, and the air inlet end of the condensation reflux system is connected to a top opening of the reactor; the condensate of the condensation reflux system flows back to the reactor, and the condensate of the vacuum condensation system flows into the vacuum liquid storage tank through the pipeline;
[0015] In the feed to the reactor, the weight ratio of the total amount of methyl ethyl ketone, platinum / alumina catalyst, cycloethylamine and phenylmonochlorosilane is 100:(0.7-1):(15-30), and the molar ratio of cycloethylamine to phenylmonochlorosilane is (2.2-2.3):1;
[0016] (2) Place the formed γ-alumina, silica gel or hydrogen-type 13X molecular sieve carrier in an oven and treat at 160-180°C for 4-6 hours, transfer it while hot to a vacuum-evacuable, atomizing nozzle-equipped, anhydrous rotary drum, seal the drum, replace it with nitrogen, maintain positive pressure and cool it to room temperature, further replace it with high-purity nitrogen and maintain positive pressure, fill it with high-purity ammonia until the pressure increases by 3-10 kPa, maintain it for 2-4 hours, until the pressure does not decrease; start the drum rotation, and spray the filtrate of step (1) onto the carrier by atomization, and the spray volume of the filtrate is 75-85% of the saturated water absorption volume of the carrier. The spraying time is 3-4 hours, and the mixture is allowed to stand for 20-40 hours for homogenization and reaction. Then, a methyl ethyl ketone solution containing 3-5wt% of methyltrichlorosilane is sprayed, and the spray volume of the methyl ethyl ketone solution of methyltrichlorosilane is 5-10% of the saturated water absorption volume of the carrier. The spraying time is 0.5-1 hour, and high-purity ammonia is charged until the pressure increases by 5-10kPa. After that, the rotation of the drum is stopped and the mixture is allowed to stand for 10-20 hours for homogenization and reaction. Finally, methyl ethyl ketone is injected for washing 2-3 times, the pressure is released, and water is injected to a positive pressure of 0.25-0.3MPa for washing for more than 5 times. After drainage and pressure release, the material is discharged to obtain an adsorbent.
[0017] Wherein, the specific surface area of the carrier is higher than 280m 2 / g, pore volume 0.7-1.0mL / g, surface hydroxyl density higher than 4 / nm 2 .
[0018] The adsorbent of the present invention, wherein the carrier in step (2) is preferably a spherical γ-alumina with a diameter of Φ2.5-3 mm or a strip-shaped γ-alumina with a diameter of Φ(1.5-2)x(3-8) mm, a hydrogen-type 13X molecular sieve, or a granular silica gel with an outer size of 3-4 mm, so as to obtain a higher airflow space velocity under the use conditions of the fixed bed adsorbent without requiring an excessively high bed inlet airflow pressure or bed pressure drop; further preferably, the carrier has an equivalent pore volume of 15-30 nm in diameter of 0.15 mL / g or more, an equivalent pore volume of 30-100 nm in diameter of 0.1 mL / g or more, and an equivalent pore volume of 100 nm or more in diameter of 0.06 mL / g or more, so that the adsorbent has a lower internal diffusion resistance and a relatively short carbon dioxide adsorption time; the surface hydroxyl density is preferably 4.5-5.5 / nm 2 ; Other indicators include: the compressive strength of the spherical carrier is higher than 60N / particle, the compressive strength of the strip carrier is higher than 120N / cm, and the abrasion is lower than 0.4wt%. The production of the carrier is a known technology in this field or related fields and can be purchased on the market or customized. The method for detecting the surface hydroxyl density is the reactive gas chromatography method in the T / FSI049-2020 method for testing the surface silanol content of fumed silica. The spherical and strip-shaped carriers are first crushed, sheared with high-speed blades, and sieved to obtain fine powder with a particle size of 44-75μm (+325 mesh to -200 mesh), and the drying conditions are changed to 180℃ for 6h.
[0019] In step (1), the condensation reflux system and the evacuation condensation system have air inlet ends a and c and air outlet ends b and d, respectively; the air inlet end a of the condensation reflux system is connected to the top interface of the reactor, and the condensate flows back to the reactor through the air inlet end a and the top interface, and the air outlet end b is connected to the air inlet end c of the evacuation condensation system; the air outlet end d of the evacuation condensation system is connected to a three-way valve and further connected to an oil-free vacuum pump.
[0020] In step (1), the platinum / alumina catalyst contains 0.1-0.2 wt% of platinum and can be prepared by the following method: a catalyst preparation container is purged and replaced with a nitrogen flow saturated with isopropanol vapor, and a catalyst with a specific surface area of 4-10 m 2 / g, a pore volume of 0.35-0.4mL / g, and an outer diameter of 44-75μm, is continuously purged and replaced with a nitrogen flow saturated with isopropanol vapor, and an isopropanol solution containing chloroplatinic acid and 300-400g / L of ethylene glycol at the required concentration is added during stirring, wherein the amount of the isopropanol solution containing chloroplatinic acid and ethylene glycol added is 25-30wt% of the saturated water absorption capacity of the alumina support. After the isopropanol solution is completely absorbed into the support (the support surface becomes dry and the fluidity is restored), the container is sealed and placed for 6-10h, then the temperature is raised to 70-80°C and dried under the condition of high-purity nitrogen flow purging at this temperature range until all the isopropanol is evaporated, the temperature is raised to 130-150°C and maintained at this temperature for 0.5-1h, and then dried under the condition of 130-150°C and high-purity nitrogen flow purging until all the ethylene glycol is evaporated, the catalyst is cooled to room temperature, and the container is sealed to obtain a platinum / alumina catalyst.
[0021] In step (1), the filtered catalyst is washed with methyl ethyl ketone for more than three times, and methyl ethyl ketone is added to prepare a slurry, which is transferred into a sealable container replaced with nitrogen and stored for later use.
[0022] In step (2), it is preferred to maintain a positive pressure of 15-30 kPa (gauge pressure) in the drum during the spraying, homogenization, reaction and methyl ethyl ketone washing to prevent oxygen and water vapor in the ambient air from penetrating into the drum and adversely affecting the grafting reaction process and effect.
[0023] The adsorbent of the present invention is suitable for use in capturing carbon dioxide from air streams or industrial gas streams in a fixed bed manner.
[0024] When the air flow with CO2 content of more than 400ppmv is used as the source of carbon dioxide, it is generally at 0-30℃, normal pressure or low positive pressure below 50kPa (gauge pressure), and the air flow velocity is higher than 2000h -1Adsorption is carried out under the conditions of , and then the adsorbed CO2 is removed by vacuum thermal desorption or atmospheric pressure thermal desorption. After the bed is cooled, air is passed through to carry out the next cycle of carbon dioxide capture operation. The desorption temperature is 90-120 ° C. The heating and cooling operations can be carried out by indirect heat exchange using heat exchange components such as coils arranged in the adsorbent bed. For example, when heating, hot water or steam is circulated in the coils, and when cooling, cold water is circulated. Steam, or hot water including boiling water, can also be introduced into the adsorbent bed alone or in addition to indirect heat exchange as a heat source for heating during desorption. When cooling, air below room temperature can also be introduced into the adsorbent bed alone or in addition to indirect heat exchange. Due to the low CO2 content in the air, the adsorption process takes several hours.
[0025] When air flow is used as the source of carbon dioxide and vacuum thermal desorption is adopted after adsorption, the adsorbent bed can be first heated to 90-100°C by indirect heat exchange and evacuated to an absolute pressure of less than 50kPa, more preferably less than 30kPa. Alternatively, the bed can be evacuated to an absolute pressure of less than 50kPa, more preferably less than 30kPa, and then heated to 90-110°C by indirect heat exchange. Finally, air or steam is introduced for purging. The exhaust gas during the heating and insulation process of the adsorbent bed and the exhaust gas during purging are cooled by indirect heat exchange and then collected through a vacuum pump, so as to obtain a carbon dioxide-rich gas stream with a CO2 content of more than 5v% or even more than 30v%.
[0026] When air flow is used as the carbon dioxide source and atmospheric pressure thermal desorption is adopted after adsorption, the adsorbent bed can be heated to 100-120°C by indirect heat exchange and then purged with air or steam. Alternatively, 100-120°C steam (which may contain CO2) can be introduced into the adsorbent bed to heat it to 100-120°C and purged. The exhaust gas during the heating and insulation process of the adsorbent bed and the exhaust gas during the purging process are collected to obtain a carbon dioxide-rich gas stream with a CO2 content of more than 3% by volume or even more than 15% by volume. When direct steam heating is used, the condensed water (including the condensed water during the heating of the adsorbent bed and the condensed water during the cooling of the removed hot gas stream) should be recycled for steam generation to avoid dissolution loss of CO2. The exhausted hot gas stream is cooled by indirect heat exchange and / or by spraying low-temperature circulating condensed water to remove most of the water vapor and reuse the condensed water. The CO2 content in the obtained carbon dioxide-rich gas stream can be more than 60% by volume or even more than 80% by volume. When using atmospheric pressure thermal desorption, circulating boiling water (which may contain CO2 bubbles) can be passed through the adsorbent bed to raise its temperature to 90-100°C and immerse the bed. The exhaust hot gas stream is cooled through indirect heat exchange and / or sprayed with low-temperature circulating condensed water, removing most of the water vapor. The resulting CO2-rich gas stream can contain over 80% CO2 by volume. The advantages of using steam and boiling water as the heat source for atmospheric pressure thermal desorption are that they can quickly expel air from the adsorbent bed, including air trapped within the adsorbent pores, and oxidation of the loaded amine is less severe than with other methods. In particular, when using steam, the height difference between the adsorbent bed and the steam generator allows for automatic thermal desorption, eliminating the need for additional mechanical force. The steam condensate can be reused for steam production. Furthermore, the small amount of water adsorbed by the adsorbent during CO2 adsorption from the air can also be thermally desorbed, condensed, and reused to supplement the normal consumption of water or boiling water for steam generation. For details, see the steam heating and circulation method in the mosquito trap below.
[0027] When an industrial gas stream with a CO2 content of more than 8% by volume is used as the source of carbon dioxide, the gas stream temperature in the adsorption stage should be lower than 40°C, preferably 10-30°C, and the gas stream pressure can be normal pressure or positive pressure. After adsorption, the pressure is reduced to an absolute pressure of less than 3 kPa, more preferably less than 1 kPa, for desorption, and then air is blown in and the next cycle of carbon dioxide capture operation is carried out, so that a carbon dioxide-rich gas stream with a CO2 content of more than 80% by volume or even more than 95% by volume can be obtained.
[0028] In the application of the adsorbent of the present invention for capturing carbon dioxide from air flow or industrial air flow, the overall process design is determined according to the air flow conditions and the requirements for the CO2 content in the resulting carbon dioxide-rich air flow, especially the selection of the desorption method and the segmentation and collection logic of the CO2-rich gas. When using air flow as the adsorption gas source, more attention should be paid to the utilization rate of CO2 removal in the desorption stage.
[0029] The beneficial effects of the present invention include: the adsorbent is a loaded amine adsorbent grafted with short-chain primary amines, the primary amine loading amount is 0.8-1.3 mol / kg and is grafted on the carrier surface through silicon-oxygen covalent bonds, the adsorbent has good heat-oxidation resistance, the loaded amine is basically not prone to oxidation and loss, it has good hydrophobicity and stable performance, and can be used in fixed bed and TVSA, TSA, and VSA modes. It can capture carbon dioxide with high efficiency from air flow or industrial air flow with a relative humidity of 30-100%, and can obtain a carbon dioxide-rich air flow with a CO2 content of more than 5v%, more than 30v%, more than 80v% or even more than 95v%; the CO2 release and capture amount in a single cycle in an air flow containing more than 400ppmv of CO2 at a relative humidity of 60-100% and an air flow containing 10v% of CO2 can exceed 0.54mol / kg adsorbent and 0.70mol / kg adsorbent, respectively, and the amine nitrogen utilization rate is higher than 0.67molCO2 / molN and 0.84molCO2 / mol, respectively. N; It is suitable for small and medium-scale carbon dioxide capture scenarios, has advantages in CO2 capture output, operating costs and service life, and its overall performance is better than existing technologies, and has certain application prospects.
[0030] From the effects of the following embodiments, it is believed that the main principles of the adsorbent of the present invention are as follows, and the above beneficial effects are also the result of the combined effects of the following principles and factors:
[0031] 1. The main reaction in step (1) is that cycloethylamine reacts with phenylmonochlorosilane (C6H5ClSiH2) to generate C6H5ClSi(C2H4NH2)2 under the conditions of anhydrous methyl ethyl ketone as reaction solvent and platinum / alumina catalyst. The yield of C6H5ClSi(C2H4NH2)2 based on phenylmonochlorosilane can reach more than 95%, and phenylmonochlorosilane is completely converted. The purpose of the subsequent vacuum distillation of the feed liquid is to remove the remaining cycloethylamine in the reaction. The filtrate has almost no amine odor and the stability is improved. If the distillation step is omitted, the filtrate has a strong amine odor, and the cycloethylamine will polymerize and block the pores during the grafting and loading reaction in step (2). The filtered catalyst is washed with methyl ethyl ketone for more than 3 times, and methyl ethyl ketone is added to make a slurry, which is transferred into a sealable container and filled with nitrogen to a positive pressure such as 15-30kPa. It can be repeatedly used after storage and has stable performance. If the filtrate is pre-processed to complete the reaction of chlorine to hydroxyl (generating C6H5OH(C2H4NH2)2), the generated ammonium chloride is difficult to remove, and dehydration dimerization between the hydroxyl groups of C6H5OHSi(C2H4NH2)2 is likely to occur, and the dimerization product cannot be grafted onto the carrier.
[0032] 2. The main reaction in step (2) is that the C6H5ClSi(C2H4NH2)2 contained in the filtrate reacts with the hydroxyl groups of the γ-alumina, silica gel or hydrogen-type 13X molecular sieve carrier through Cl, under the neutralization effect of sufficient ammonia, and the C6H5Si(C2H4NH2)2 group is grafted to the inner and outer surfaces of the carrier in the form of Si-O-Si or Si-O-Al covalent bonds, and the hydroxyl density on the carrier surface is higher than 4 / nm 2 The grafting amount depends on the mutual steric hindrance of the C6H5Si(C2H4NH2)2 groups. The grafting is uniform and the loading is relatively large (the density of surface hydroxyl groups is low, such as less than 1.5 / nm). 2 The grafting is sometimes uneven, and some positions cannot be grafted, resulting in a decrease in the total loading capacity). The actual grafting amount is close to the theoretical grafting amount. When a hydrogen-type 13X molecular sieve carrier is used, the grafting is basically in the "cage" of its structure rather than in the pores between cages (no significant internal diffusion restriction is found); the remaining hydroxyl groups of the carrier react with methyltrichlorosilane under the neutralization of sufficient ammonia, and the CH3Si groups are grafted to a large proportion of the remaining inner and outer surfaces of the carrier in the form of covalent bonds of Si-O-Si or Si-O-Al; in the subsequent washing process with methyl ethyl ketone solution, a small amount of organic silicon that has not been grafted is basically removed, eliminating the problem of accumulation and pore blocking in the subsequent preparation and application of the adsorbent; in the process of injecting water to a positive pressure of 0.2-0.3MPa to wash the methyl ethyl ketone and generate ammonium chloride in the grafting reaction, the adsorbent gradually has It has a certain hydrophobicity (but water with a positive pressure of more than 0.2MPa can be pressed into the inner pores), and the obtained adsorbent does not wet and absorb pressureless water at 20-40℃; it only absorbs a small amount of moisture (2-3wt%) in an air flow of saturated water vapor at 20-40℃, and it is believed that basically no aqueous solution is formed in the inner pores. This is the basis for the adsorbent to adsorb carbon dioxide in an air flow with a relative humidity of 90-100% without decreasing its adsorption performance; in the heating or constant temperature process of thermal desorption using steam or boiling water at normal pressure of 100-120℃, it is found that its hydrophobicity can still be maintained, otherwise it is easy to cause the adsorbent to gradually pulverize or break; steam can be used for CO2 desorption and desorption, which is an important reason for being able to capture a carbon dioxide-rich air flow with a CO2 content of more than 80v% or even more than 95v% from the air flow.
[0033] 3. In the adsorbent prepared in step (2), the C6H5Si(C2H4NH2)2 group and CH3Si group are grafted and loaded by covalent bonding via Si-O-Si or Si-O-Al. The former (C6H5Si(C2H4NH2)2 group) is a short-chain organic amine with good thermal stability and oxidation resistance (stable under conventional hydrothermal conditions below 150°C), has low steric hindrance when adsorbing CO2, is distributed on the surface of the inner pores, is easy to play a role, and has little effect on the diffusion of CO2. Therefore, compared with the prior art (including modified MOF), the adsorbent of the present invention can adsorb CO2 at a rate of 50% or even more than 100% faster in the adsorption process, and can desorb CO2 at a rate of more than 30% faster in the desorption process. The CH3Si group occupies less space, offers improved thermal stability and oxidation resistance, and has little effect on the internal diffusion of CO2. Because the support surface is largely shielded by the CH3Si group, it is less susceptible to changes such as recrystallization under steam conditions, a problem that is often difficult to avoid on silica supports, especially silica gel supports. Because the CH3Si group eliminates a large proportion of residual hydroxyl groups and acts as a shield, the primary amine groups of the supported amine cannot or have difficulty contacting the support surface, meaning they cannot or have difficulty interacting with certain remaining active sites on the support surface, such as through adsorption. This allows the adsorbent to maximize its CO2 adsorption capacity and is less susceptible to oxidation by residual O2 during temperature desorption. Furthermore, the C2H4NH2 group in the C6H5Si(C2H4NH2)2 group is a primary amine group, which exhibits moderate binding strength with CO2 and H2O, resulting in strong adsorption and binding, yet still readily desorbs (compared to secondary amine groups). Therefore, this adsorbent performs well in the aforementioned CO2 capture application, is very stable, and has a long lifespan.
[0034] The present invention also provides a mosquito trap that adopts the adsorbent and utilizes air flow as a carbon dioxide gas source; the mosquito trap comprises a carbon dioxide capture system, a mosquito catching system, and a control system; the carbon dioxide capture system comprises an adsorbent tank and related components, the adsorbent of the present invention is filled in the adsorbent tank in a fixed bed manner, and a carbon dioxide-rich gas flow is generated by the above-mentioned carbon dioxide capture method; the carbon dioxide-rich gas flow generated by the carbon dioxide capture system is continuously or intermittently sent to the mosquito catching system for utilization; the control system controls the operation of the carbon dioxide capture system and the mosquito catching system according to a set program.
[0035] The carbon dioxide capture system, wherein the adsorbent tank can be filled with adsorbent, for example, 2-10 L, and related components are arranged according to the carbon dioxide capture method.
[0036] The mosquito trapping system may have or utilize existing mosquito trapping structures and operating methods. Preferably, the system comprises a mosquito attracting module, a switchable electric damper (damper), a mosquito trapping and storage module, and a rear-suction fan. The mosquito trapping and storage module includes a mosquito net box. The mosquito trapping mechanism operates by drawing mosquitoes attracted by a mixture of carbon dioxide-rich gas and air into the mosquito net box along with the strong wind generated by the suction fan.
[0037] The mosquito trap has a good mosquito catching effect in summer and autumn when the relative humidity of the air is above 40%, including hot and humid days with a relative humidity of 90-100%. That is, the amount and concentration of carbon dioxide captured required for catching mosquitoes do not change significantly with changes in the relative humidity of the air. The mosquito trap is suitable for semi-enclosed places such as indoors and open places outdoors. DETAILED DESCRIPTION
[0038] The technical solution of the present invention is described and illustrated in detail below with reference to the embodiments. Example 1
[0039] The adsorbent for capturing carbon dioxide from air or industrial gas streams of this embodiment is prepared by following the steps below:
[0040] (1) A 1500 mL glass reactor (three-necked flask) and its accompanying condensation reflux system and evacuation condensation system were subjected to anhydrous treatment and 99.9% nitrogen replacement; anhydrous methyl ethyl ketone was injected into the reactor as a reaction solvent, and a powdered platinum / aluminum oxide hydrosilylation reaction catalyst was added. The reaction was continued with stirring, and anhydrous cyclohexylamine was injected. The reactor feed liquid temperature was controlled at 35-40°C and the condensation temperature of the condensation reflux system was controlled at -15 to -20°C; phenyl monochlorosilane was continuously injected and the injection time was controlled at 4 hours. After that, the feed liquid continued to react for 4 hours. The reaction was then controlled. The feed liquid temperature in the reactor is 35-40°C, the condensation temperature of the condensation reflux system is 0°C, the condensation temperature of the evacuated condensation system is -20°C, and the required vacuum degree is maintained. The reactor feed liquid is distilled for 0.5h and the distillation removal amount of the feed liquid is controlled to be 12-13wt% to evaporate the remaining cycloethylamine; the distilled feed liquid in the reactor is filtered under anhydrous and air-tight conditions, and the filtrate is used as the spray impregnation liquid for the adsorbent in step (2); the filtered catalyst is washed with methyl ethyl ketone for more than 3 times, and methyl ethyl ketone is added to prepare a slurry, which is transferred into a nitrogen-substituted, sealable container and stored for later use;
[0041] The condensation reflux system and the evacuation condensation system respectively have air inlet ends a and c and air outlet ends b and d; the air inlet end a of the condensation reflux system is connected to a top interface of the reactor, and the condensate flows back to the reactor through the air inlet end a and the top interface, and the air outlet end b is connected to the air inlet end c of the evacuation condensation system; the condensate of the evacuation condensation system flows into the vacuum liquid storage tank through a pipeline, and the air outlet end d is connected to a three-way valve and further connected to an oil-free vacuum pump;
[0042] The total amount of methyl ethyl ketone, platinum / alumina catalyst, cycloethylamine, and phenylmonochlorosilane fed to the reactor was 924 g (800 g, 6.0 g, and 140 g, respectively), with a weight ratio of 100:0.75:17.5, and a molar ratio of cycloethylamine to phenylmonochlorosilane of 2.25:1.
[0043] (2) Spherical γ-alumina carrier (Φ2.6-2.8mm, specific surface area 283m 2 / g, pore volume 0.74mL / g, 15-30nm equivalent diameter pore volume 0.17mL / g, 30-100nm equivalent diameter pore volume 0.10mL / g, 100nm equivalent diameter pore volume 0.07mL / g, surface hydroxyl density 4.6 / nm 2 , compressive strength 88N / particle, abrasion 0.29wt%) 1308g, put it into a thin layer on a stainless steel plate, put it in an oven and treat it at 170℃ for 5h, weigh 1000g while it is hot and transfer it to a vacuum-evacuable, atomizing nozzle, and an anhydrous drum (content volume 9.6L), seal the drum, evacuate it to an absolute pressure of 10kPa and fill it with 99.5% nitrogen to a positive pressure of 10kPa and repeat the operation 3 times for replacement (to remove air and contained water vapor), maintain positive The pressure is 10kPa and cooled to room temperature, evacuated to an absolute pressure of 10kPa and filled with 99.9% nitrogen to a positive pressure of 10kPa for further replacement (deoxygenation) and maintained at a positive pressure of 10kPa, filled with 99.9% ammonia to a positive pressure of 16kPa (an increase of 6kPa relative to before ammonia filling), and maintained at this pressure for 3h (the drum is started to rotate for 5min every 30min) until the pressure does not decrease and drops to room temperature (part of the ammonia introduced is adsorbed on the inner and outer surfaces of the carrier to combine with Start the drum rotation and spray 689 mL of the filtrate of step (1) onto the carrier (the spray volume of the filtrate is 85% of the saturated water absorption volume of 810 mL of the carrier). The spraying time is 3.3 h. After standing for 30 h for homogenization and reaction, 65 mL of methyl ethyl ketone solution containing 4 wt% of methyltrichlorosilane is sprayed. The spray volume of the methyl ethyl ketone solution of methyltrichlorosilane is 8% of the saturated water absorption volume of the carrier. The spraying time is 0.5 h. High-purity ammonia is added until the pressure rises to 8kPa, then the rotation of the drum is stopped and allowed to stand for 15 hours for homogenization and reaction; finally, methyl ethyl ketone (3500-3600g each time) is injected for washing 3 times (try to remove a small amount of silicone that has not been grafted and eliminate its accumulation and pore blocking problem), the pressure is released, and pure water is injected to a positive pressure of 0.25MPa in the drum, and the drum is started to rotate for 0.5h, drained, and washed with water 5 times (to wash away the ammonium chloride generated by the reaction), and the material is discharged after drainage and pressure release to obtain the adsorbent.
[0044] In step (1), the platinum / alumina catalyst used contains 0.15 wt% platinum and is prepared by the following method: the catalyst preparation container is a 100 mL three-necked glass flask, which is fixed on an electric magnetic stirrer with precise temperature control, a stirrer is placed, a mercury thermometer is installed, and a 99.9% nitrogen mixed gas saturated with isopropanol is introduced for replacement (60 mL / min, 30 min), the gas is stopped, and a 6.7 m3 specific surface area is added. 2 / g, pore volume 0.38mL / g, 44-75μm outer diameter alumina carrier (+325 mesh to -200 mesh), then introduce 99.9% nitrogen mixed gas saturated with isopropanol for replacement (30mL / min, 10min, the distance between the gas outlet and the bottom of the flask is 30mm), stop the gas, seal the flask, start stirring, and use a 2mL syringe and microporous needle to uniformly add 1.2mL of isopropanol solution containing 26.3g / L of chloroplatinic acid (H2PtCl6) and 350g / L of ethylene glycol (drip time The reaction mixture was stirred for 3 minutes, and the amount of isopropanol solution added was 30 wt% of the saturated water absorption rate of the alumina support of 0.40 mL / g). After all the isopropanol solution was absorbed (the powder fluidity was restored), stirring was stopped, and the flask was placed in a sealed manner for 8 hours. After that, 99.9% nitrogen (30 mL / min) was continuously introduced. The temperature was raised to 75°C and dried at this temperature for 3 hours, the temperature was raised to 145°C and kept constant at this temperature for 0.5 hours, and then dried at 145°C for 3 hours (all the ethylene glycol was evaporated), cooled to room temperature, nitrogen was stopped, and the flask was sealed to obtain a platinum / alumina catalyst.
[0045] The adsorbent prepared in this example for capturing carbon dioxide from air or industrial gas streams was tested to float on pure water at room temperature and a positive pressure of 0-106 kPa, and on pure water at 100°C and a positive pressure of 0-73 kPa, demonstrating good overall hydrophobicity. The adsorbent exhibited a total weight loss of 2.3 wt% when dried at 130°C for 4 hours under air conditions, and 2.4 wt% after a further 100 hours of drying. The adsorbent also exhibited minimal odor, which was completely eliminated after purging with room temperature air for 6 hours. Consequently, the water content was less than 2.4 wt%. The nitrogen content, as determined by chemical analysis, was 0.81 mol / kg. Example 2
[0046] The preparation conditions and other raw materials of Example 1 were used and the operations of steps (1) to (2) of Example 1 were basically repeated to prepare the adsorbent for capturing carbon dioxide from air flow or industrial air flow of this embodiment. The main differences were as follows: in step (1), the total amount of methyl ethyl ketone, platinum / alumina catalyst, cycloethylamine and phenylmonochlorosilane in the feed of the glass reactor was 1048 g (800 g, 8.0 g and 240 g, respectively), the weight ratio was 100:1:30, and the molar ratio of cycloethylamine to phenylmonochlorosilane was 2.20:1; the platinum / alumina catalyst 8.0 g used was obtained by weighing 2.0 g of the unused 4 g of the 10 g catalyst prepared in Example 1 and adding the 6.0 g of the catalyst in the methyl ethyl ketone filtered out and preserved in step (1); in step (2), the carrier treated in an oven at 170°C was a Φ mm spherical hydrogen-type 13X molecular sieve (Φ2.7-3.0 mm, specific surface area 583 m 2 / g, pore volume 0.77mL / g, 15-30nm equivalent diameter pore volume 0.15mL / g, 30-100nm equivalent diameter pore volume 0.10mL / g, 100nm equivalent diameter pore volume 0.06mL / g, surface hydroxyl density 4.8 / nm 2 , compressive strength 72N / particle, abrasion 0.33wt%) 1400g; filled with 99.9% ammonia to a positive pressure of 20kPa (increased by 10kPa relative to before ammonia filling), and sprayed with 672mL of the filtrate prepared in step (1) (the filtrate spraying volume is 80% of the saturated water absorption volume of 840mL of the carrier).
[0047] The adsorbent prepared in this example for capturing carbon dioxide from air or industrial gas streams was tested to float on pure water at room temperature and a positive pressure of 0-92 kPa, and on pure water at 100°C and a positive pressure of 0-65 kPa, demonstrating good overall hydrophobicity. The adsorbent exhibited a total weight loss of 2.6 wt% when dried at 130°C for 4 hours under air conditions, and 2.7 wt% after 100 hours of drying. The adsorbent also exhibited minimal odor, which was completely eliminated after purging with room temperature air for 6 hours. Consequently, the water content was less than 2.7 wt%. The nitrogen content, as determined by chemical analysis, was 1.22 mol / kg. Example 3
[0048] The preparation conditions and other raw materials of Example 1 were used and the operations of steps (1)-(2) of Example 2 were basically repeated to prepare the adsorbent for capturing carbon dioxide from air flow or industrial air flow of this embodiment. The main differences were as follows: in step (1), the total amount of methyl ethyl ketone, platinum / alumina catalyst, cycloethylamine and phenylmonochlorosilane in the feed of the glass reactor was 968 g (800 g, 8.0 g and 200 g, respectively), the weight ratio was 100:1:25, and the molar ratio of cycloethylamine to phenylmonochlorosilane was 2.20:1; the platinum / alumina catalyst 8.0 g was the catalyst in the methyl ethyl ketone filtered out and preserved in step (1) of Example 2; the carrier used in step (2) was granular silica gel (spherical, with a specific surface area of 392 m 2 / g, pore volume 0.93mL / g, 15-30nm equivalent diameter pore volume 0.20mL / g, 30-100nm equivalent diameter pore volume 0.13mL / g, 100nm equivalent diameter pore volume 0.08mL / g, surface hydroxyl density 5.5 / nm 2 , compressive strength 64N / particle, abrasion 0.25wt%) 1500g; spraying step (1) prepared filtrate 735mL (the filtrate spraying volume is 75% of the carrier saturated water absorption volume 980mL).
[0049] The adsorbent prepared in this example for capturing carbon dioxide from air or industrial gas streams was tested to float on pure water at room temperature and a positive pressure of 0-117 kPa, and on pure water at 100°C and a positive pressure of 0-89 kPa, demonstrating good overall hydrophobicity. The adsorbent exhibited a total weight loss of 2.0 wt% when dried at 130°C for 4 hours under air conditions, and 2.1 wt% after 100 hours of drying. The adsorbent also exhibited minimal odor, which was completely eliminated after purging with room temperature air for 6 hours. Consequently, the water content was less than 2.1 wt%. The nitrogen content, as determined by chemical analysis, was 1.04 mol / kg. Example 4
[0050] 300 mL of each of the adsorbents prepared in Examples 1-3 were taken and used in turn in a small laboratory evaluation device for carbon dioxide capture experiments. The adsorbent was loaded into a vertical, transparent hard glass tube (with a glass jacket for water insulation) with a height of 320 mm and an inner diameter of 40 mm. The adsorbent bed height was about 240 mm (a height-to-diameter ratio of about 6). The airflow during adsorption and desorption was both upward and downward. Simulated air flow and simulated industrial airflow were prepared separately by the gas distribution system, and the exhaust gas after adsorption was pressurized by a circulating fan and returned to the gas distribution system for utilization. Each adsorbent was used to adsorb CO2 in the manner shown in Table 1 below.
[0051] During the capture cycle 0-4, the desorption process after CO2 adsorption with simulated air flow as the source of CO2 gas is carried out, the jacket is passed through with sufficient flow of 100℃ atmospheric pressure steam, which is different from the source of steam in the tube, and the tube is purged with 100-103℃ atmospheric pressure steam for 10-15min (occurred by the complete vaporization of pure water at a flow rate of 15g / min). The gas and airflow discharged from the tube are cooled to 23-25℃ through the condenser, and the condensed water is separated and removed, and then collected in a latex bag. When the gas volume in the latex bag does not increase, it is maintained for 5 minutes and then the latex bag inlet is sealed to end the desorption process. The dead volume of the air flow path in the condenser is 110mL; during the bed cooling process, the jacket is passed through with sufficient flow of 25℃ water, and the tube is purged with 25℃ atmospheric pressure air at a flow rate of 25L / min for 30-60min, and the cooling process is ended when the exhaust temperature is lower than 30℃.
[0052] During the desorption process after capture cycles 6-9, when simulating industrial airflow as the CO2 gas source for adsorption, the jacket is still empty (water-free) and a micro oil-free vacuum pump is used to evacuate the tube to an absolute pressure of 2-3 kPa (without heating). The exhausted gas and airflow are cooled to 23-25°C by the above-mentioned condenser and the condensed water is separated and removed before being collected in a latex bag. When the gas volume in the latex bag does not increase, a room temperature and normal pressure air flow of 50 mL / min is passed through the tube to purge for 10 minutes and continue to evacuate to maintain an absolute pressure of 5-10 kPa. The inlet of the latex bag is sealed and the vacuum pump is turned off at the same time. After the pressure in the tube rises to normal pressure, the purge air is turned off to end the desorption process. After the desorption process is completed, the next cycle of carbon dioxide capture operation is carried out directly.
[0053] After the capture cycles 0-9 of each adsorbent are completed, the capture cycles 1-9 are repeated once, and then the capture cycle 4 is repeated ten times, for a total of 29 capture cycles, and finally the adsorbent is discharged.
[0054] The volume and CO2 content of the carbon dioxide-rich gas stream collected by the latex bag in each capture cycle were measured, and the CO2 capture capacity (mol CO2 / kg adsorbent) and amine nitrogen utilization rate (mol CO2 / mol N) of the adsorbent were calculated respectively.
[0055] Table 1 Adsorption conditions for carbon dioxide capture experiments
[0056]
[0057] The results of the carbon dioxide capture experiments of the above adsorbents are as follows: when the simulated air flow is used as the carbon dioxide source, the CO2 content in the carbon dioxide-rich airflow collected by the latex bag in each capture cycle of each adsorbent is above 95v% (dry basis), the CO2 capture amount of a single capture cycle is calculated to be more than 0.57mol / kg adsorbent, and the amine nitrogen utilization rate is higher than 0.70molCO2 / molN. Moreover, the relative difference in the CO2 capture amount and amine nitrogen utilization rate of each adsorbent under the different relative humidity airflow conditions of 60%, 75%, 90% and 100% is less than 4.5%; when the industrial airflow is used as the carbon dioxide source, the CO2 content in the carbon dioxide-rich airflow collected by the latex bag in each capture cycle of each adsorbent is above 90v% (dry basis), the CO2 capture amount of a single capture cycle is more than 0.72mol / kg adsorbent, and the amine nitrogen utilization rate is higher than 0.85molCO2 / mol N, and the relative differences in CO2 capture and amine nitrogen utilization for each adsorbent under the aforementioned airflow conditions of 60%, 75%, 90%, and 100% relative humidity were all less than 6.3%. Each adsorbent recaptured the same capture efficiency as in the first capture cycles 1-9 during repeated capture cycles 1-9. Each adsorbent also recaptured the same capture efficiency as in the first and second capture cycles 4 during the final ten repetitions of capture cycle 3. Inspection of each adsorbent after discharge and flattening on a plastic tray revealed no signs of breakage or pulverization, and its appearance remained unchanged from pre-use.
[0058] Afterwards, 300 mL of the adsorbent from Example 3 (granular silica gel grafted with a short-chain organic amine and hydrophobically treated), which had demonstrated good overall performance after 29 capture cycles and had been discharged, was refilled into the glass tube of the evaluation apparatus. The capture cycle 3 was repeated 31 times, for a total of 60 capture cycles, before the adsorbent was discharged. During the 30th to 60th capture cycles, the adsorbent consistently achieved the same CO2 capture performance as in the first and second capture cycles 3. The adsorbent was discharged and flattened on a plastic tray for inspection, revealing no cracking or pulverization, and its appearance remained unchanged from before use.
[0059] The experimental results of carbon dioxide capture in this embodiment show that the above three adsorbents have good heat-oxidation resistance, the loaded amine is basically not prone to oxidation and loss, the moisture absorption is low, the hydrophobicity is good, the performance is stable, the CO2 adsorption speed is fast and the adsorption amount is less affected by humidity, the gas production concentration is high, the gas production in the same time is not low, the carbon dioxide capture effect is good, and it has advantages in CO2 capture output (unit time and unit adsorption tower volume combined), operating costs and service life. The overall performance is better than the existing technology and has certain application prospects. Example 5
[0060] Three commercially available mosquito traps that use air flow as a carbon dioxide gas source were modified by replacing the adsorbent in the fixed bed of their adsorbent tanks with an equal volume of the adsorbent (freshly prepared) from Example 3 (each mosquito trap has two adsorbent tanks, each containing approximately 1.1 L of adsorbent). No other modifications were made, and the carbon dioxide desorption method was still atmospheric pressure heating and air purge desorption, and these mosquito traps served as the mosquito traps of this embodiment.
[0061] The mosquito traps before and after modification both have a carbon dioxide capture system, a mosquito catching system and a control system; the carbon dioxide capture system includes an adsorbent tank and related components, the adsorbent is filled in the adsorbent tank in a fixed bed manner, and a carbon dioxide-rich airflow is generated by normal pressure heating and desorption; the carbon dioxide-rich airflow generated by the carbon dioxide capture system is intermittently sent to the mosquito catching system for use; the control system controls the operation of the carbon dioxide capture system and the mosquito catching system according to a set program; the structure of the mosquito catching system includes a mosquito attracting module, a switch-type electric damper, a mosquito catching and killing storage module and a rear-suction fan, and the mosquito catching and killing storage module has a mosquito net box; the mosquito catching system sucks mosquitoes attracted by the mixture of carbon dioxide-rich gas and air into the mosquito net box along with the strong wind generated by the suction fan.
[0062] The modified mosquito trap has a good mosquito catching effect when placed in semi-enclosed indoor and outdoor open places in summer and autumn when the relative humidity of the air is above 40%, including hot and humid days with a relative humidity of 90-100%. That is, the capture amount and capture concentration of carbon dioxide required for catching mosquitoes do not change significantly with changes in the relative humidity of the air.
[0063] Before the modification, the mosquito traps were effective at 50-85% relative humidity, but saw a slight decrease above 85% and a sharp drop above 95%. Based on the instructions for use, chemical composition analysis of the removed adsorbents, and actual mosquito-catching performance, one of the traps contained a carbonate-loaded adsorbent, while the other two contained an organic amine polymer-loaded adsorbent. These adsorbents exhibited a maximum moisture absorption rate exceeding 7% by weight at 25°C and 90% relative humidity. They were all hydrophilic, with saturated water absorption exceeding 12% by weight in a 250mL beaker of water.
[0064] In the present invention, the unit of CO2 content ppmv is one millionth by volume, and v% is one percent by volume; the specific surface area of the carrier is determined by the low-temperature nitrogen adsorption BET method, and the pore volume and its distribution are obtained by coupling the measurement results of the low-temperature nitrogen adsorption BET method and the mercury intrusion method.
Claims
1. An adsorbent for capturing carbon dioxide from an air stream or an industrial gas stream, prepared by the following steps: (1) The reactor and its attached condensation reflux system and evacuation condensation system are subjected to anhydrous treatment and nitrogen replacement; anhydrous methyl ethyl ketone is injected into the reactor as a reaction solvent, a powdered platinum / alumina catalyst is added, and the mixture is continuously stirred, and anhydrous cycloethylamine is injected, and the feed liquid temperature in the reactor is controlled to be 35-40°C, and the condensation temperature of the condensation reflux system is controlled to be -15 to -20°C; phenyl monochlorosilane is continuously injected and the injection time is controlled to be 3-5h, and then the feed liquid continues to react for 4-5h; the feed liquid temperature in the reactor is then controlled to be 25-40°C, the condensation temperature of the condensation reflux system is controlled to be 0 to 5°C, the condensation temperature of the evacuation condensation system is controlled to be -15 to -20°C, and the required vacuum degree is controlled, and the reactor feed liquid is distilled for 0.5-1h and the distillation removal amount of the feed liquid is controlled to be 10-15wt%; the distilled feed liquid in the reactor is filtered under water-free and air-tight conditions, and the filtrate is used as the spray impregnation liquid of the adsorbent in step (2); in, The condensation reflux system and the vacuum condensation system are used in series, and the air inlet end of the condensation reflux system is connected to a top opening of the reactor; the condensate of the condensation reflux system flows back to the reactor, and the condensate of the vacuum condensation system flows into the vacuum liquid storage tank through the pipeline; In the feed of the reactor, the weight ratio of the total amount of methyl ethyl ketone, platinum / alumina catalyst, cycloethylamine and phenylmonochlorosilane is 100:(0.7-1):(15-30), and the molar ratio of cycloethylamine to phenylmonochlorosilane is (2.2-2.3):1; (2) The formed γ-alumina, silica gel or hydrogen-type 13X molecular sieve carrier is placed in an oven and treated at 160-180°C for 4-6 hours, and while hot, is transferred to a vacuum-evacuable, atomizing nozzle-equipped, anhydrous rotary drum, and the drum is sealed, replaced with nitrogen, maintained at a positive pressure, and cooled to room temperature, and further replaced with nitrogen and maintained at a positive pressure, and ammonia is filled until the pressure increases by 3-10 kPa, and maintained for 2-4 hours until the pressure does not decrease; the drum is started to rotate, and the filtrate of step (1) is sprayed onto the carrier in an atomized manner, and the spraying volume of the filtrate is 75-85% of the saturated water absorption volume of the carrier, and the spraying The time is 3-4 hours, and the drum is allowed to stand for 20-40 hours for homogenization and reaction, and then a methyl ethyl ketone solution containing 3-5wt% of methyl trichlorosilane is sprayed, and the spraying volume of the methyl ethyl ketone solution of methyl trichlorosilane is 5-10% of the saturated water absorption volume of the carrier. The spraying time is 0.5-1 hour, and ammonia is charged until the pressure increases by 5-10kPa, and then the rotation of the drum is stopped, and the drum is allowed to stand for 10-20 hours for homogenization and reaction; finally, methyl ethyl ketone is injected for washing 2-3 times, and the pressure is released, and water is injected to a positive pressure of 0.25-0.3MPa and washed for more than 5 times, and the material is discharged after drainage and pressure release to obtain an adsorbent; Wherein, the specific surface area of the carrier is higher than 280m 2 / g, pore volume 0.7-1.0mL / g, surface hydroxyl density higher than 4 / nm 2 .
2. The adsorbent according to claim 1, characterized in that The carrier in step (2) is a spherical material with a diameter of 2.5-3 mm or a strip-shaped material with a diameter of (1.5-2) x (3-8) mm, a hydrogen-type 13X molecular sieve, or a granular silica gel with an outer size of 3-4 mm.
3. The adsorbent according to claim 2, characterized in that The carrier in step (2) has an equivalent pore volume of 15-30 nm in diameter of more than 0.15 mL / g, an equivalent pore volume of 30-100 nm in diameter of more than 0.1 mL / g, and an equivalent pore volume of more than 100 nm in diameter of more than 0.06 mL / g, and a surface hydroxyl density of 4.5-5.5 / nm 2 The compressive strength of the spherical carrier is higher than 60N / particle, the compressive strength of the strip carrier is higher than 120N / cm, and the abrasion is lower than 0.4wt%.
4. The adsorbent according to claim 1, characterized in that In step (1), the platinum / alumina catalyst contains 0.1-0.2 wt% platinum and is prepared by the following method: a catalyst preparation container is purged and replaced with a nitrogen flow saturated with isopropanol vapor, and a catalyst having a specific surface area of 4-10 m 2 / g, a pore volume of 0.35-0.4mL / g, and an outer diameter of 44-75μm, continue to purge and replace with a nitrogen flow saturated with isopropanol vapor, add an isopropanol solution containing chloroplatinic acid and 300-400g / L of ethylene glycol at the required concentration during stirring, the amount of the isopropanol solution containing chloroplatinic acid and ethylene glycol added is 25-30wt% of the saturated water absorption of the alumina carrier, after the isopropanol solution is completely absorbed by the carrier, the container is sealed and placed for 6-10h, then the temperature is raised to 70-80℃ and dried under the condition of purging with high-purity nitrogen flow at this temperature range until all the isopropanol is evaporated, the temperature is raised to 130-150℃ and kept at a constant temperature for 0.5-1h, and then dried under the temperature range of 130-150℃ and purging with high-purity nitrogen flow until all the ethylene glycol is evaporated, cooled to room temperature, and the container is sealed to obtain a platinum / alumina catalyst.
5. The method for using the adsorbent according to claim 1, characterized in that: When capturing carbon dioxide from air flow in a fixed bed, the adsorption stage is at 0-30°C, atmospheric pressure or low positive pressure below 50kPa, and air flow velocity of 2000-5000h -1 The process is carried out under the conditions of vacuum thermal desorption or atmospheric pressure thermal desorption to remove the adsorbed CO2 at a desorption temperature of 90-120°C to obtain a carbon dioxide-rich gas stream; finally, the bed is cooled to carry out the next cycle of carbon dioxide capture operation.
6. The adsorbent application method according to claim 5, characterized in that: During the vacuum thermal desorption operation, the adsorbent bed is first heated to 90-100°C by indirect heat exchange and evacuated to an absolute pressure below 50 kPa, or first evacuated to an absolute pressure below 50 kPa and then heated to 90-110°C by indirect heat exchange, and then air or steam is introduced for purging; the exhaust gas during the heating and insulation process of the adsorbent bed and the exhaust gas during purging are collected, cooled by indirect heat exchange, and then fed into a vacuum pump to obtain a carbon dioxide-rich gas flow at the outlet of the vacuum pump.
7. The adsorbent application method according to claim 5, characterized in that: During the atmospheric pressure thermal desorption operation, 100-120°C steam is introduced into the adsorbent bed alone or on the basis of indirect heat exchange as a heating heat source and a purge gas; the exhaust gas during the heating and insulation process of the adsorbent bed and the exhaust gas during the purge are collected, the temperature is lowered by indirect heat exchange, the condensed water is separated, and a carbon dioxide-rich gas flow is obtained. The condensed water is recycled for steam generation, and the excess condensed water is discharged.
8. The method for using the adsorbent according to claim 1, characterized in that: When capturing carbon dioxide from an industrial gas stream with a CO2 content of more than 8% by volume in a fixed bed mode, the gas stream temperature in the adsorption stage is 10-30°C, and the gas stream pressure is normal pressure or positive pressure. After adsorption, the pressure is reduced to an absolute pressure below 3kPa for desorption to obtain a carbon dioxide-rich gas stream with a CO2 content of more than 80% by volume, which is then purged with air and the next cycle of carbon dioxide capture operation is carried out.
9. A mosquito trap, comprising a carbon dioxide capture system, a mosquito trap system and a control system; the carbon dioxide capture system comprises an adsorbent tank and related components, and generates a carbon dioxide-rich gas flow by any method as described in claims 5-7, the adsorbent tank is filled with any adsorbent as described in claims 1-3 in a fixed bed manner, and related components are arranged according to the carbon dioxide capture method; the carbon dioxide-rich gas flow generated by the carbon dioxide capture system is continuously or intermittently sent to the mosquito trap system for use; the control system controls the operation of the carbon dioxide capture system and the mosquito trap system according to a set program.
10. The mosquito trap according to claim 9, characterized in that: The mosquito catching system structurally comprises a mosquito attracting module, a switch type electric damper, a mosquito catching and killing storage module and a rear suction fan. The mosquito catching and killing storage module has a mosquito catching net box. The mosquito catching system attracts mosquitoes attracted by a mixture of carbon dioxide-rich gas and air into the mosquito catching net box along with the strong wind generated by the suction fan.